Progression of chronic kidney disease among black patients attending a tertiary hospital in Johannesburg, South Africa - Meremo, Alfred; Paget, Graham; Duarte, Raquel; Bintabara, Deogratius; Naicker, Saraladevi (PloS one, 2023)
Chronic kidney disease (CKD) is a major public health issue worldwide and is an important contributor to the overall non-communicable disease burden. Chronic kidney disease is usually asymptomatic, and insidiously and silently progresses to advanced stages in resource limited settings. A prospective longitudinal study was carried out on black patients with CKD attending the kidney outpatient clinic at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) in South Africa, between September 2019 to March 2022. Demographic and clinical data were extracted from the ongoing continuous clinic records, as well as measurements of vital signs and interviews at baseline and at follow up. Patients provided urine and blood samples for laboratory investigations as standard of care at study entry (0) and at 24 months, and were followed up prospectively for two (2) years. Data were descriptively and inferentially entered into REDcap and analysed using STATA version 17, and multivariable logistic regression analysis was used to identify predictors of CKD progression. A total of 312 patients were enrolled into the study, 297 (95.2%) patients completed the study, 10 (3.2%) patients were lost to follow and 5 (1.6%) patients died during the study period. The prevalence of CKD progression was 49.5%, while that of CKD remission was 33% and CKD regression was 17.5%. For patients with CKD progression the median age at baseline was 58 (46-67) years, the median eGFR was 37 (32-51) mL/min/1.73 m2, median urine protein creatinine ratio (uPCR) was 0.038 (0.016-0.82) g/mmol and the median haemoglobin (Hb) was 13.1 (11.7-14.4) g/dl; 95.2% had hypertension, 40.1% patients had diabetes mellitus and 39.5% had both hypertension and diabetes mellitus. Almost half (48.3%) of patients with CKD progression had severely increased proteinuria and 45.6% had anaemia. Variables associated with higher odds for CKD progression after multivariable logistic regression analysis were severely increased proteinuria (OR 32.3, 95% CI 2.8-368.6, P = 0.005), moderately increased proteinuria (OR 23.3, 95% CI 2.6-230.1, P = 0.007), hypocalcaemia (OR 3.8, 95% CI 1.0-14.8, P = 0.047), hyponatraemia (OR 4.5, 95% CI 0.8-23.6, P = 0.042), anaemia (OR 2.1, 95% CI 1.0-4.3, P = 0.048), diabetes mellitus (OR 1.8, 95% CI 0.9-3.6, P = 0.047), elevated HbA1c (OR 1.8, 95% CI 1.2-2.8, P = 0.007) and current smoking (OR 2.8, 95% CI 0.9-8.6, P = 0.049). Our study identified a higher prevalence of CKD progression in a prospective longitudinal study of black patients with CKD compared with literature reports. CKD Progression was associated with proteinuria, diabetes mellitus, elevated HbA1c, anaemia, hypocalcaemia, hyponatraemia and current smoking in a cohort of black patients with CKD who had controlled hypertension and diabetes mellitus at baseline.